Analisis Prosedur Dokumen Export Cargo Abrasive Cloth oleh PPJK PT Millennium Trans Bahari - Shalma Thania Putri; Iswati Iswati; Eny Sulistyowati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Export activities are the activity of removing goods from within the country to the destination country. So exports are trade by sending goods to a country with which there has previously been an agreement by each representative of the country concerned, namely the exporter and importer. The smoothness of the export process can be seen from the document handling procedures carried out by PPJK so that the cargo can enter the customs area without any problems occurring. The aim of this research is to analyze the export document procedures for abrasive cloth cargo by PT. Millennium Trans Bahari as PPJK. In writing this thesis, research was carried out using a qualitative approach through direct observation methods at PT. Millennium Trans Bahari, interview method with one of the operational staff and documentation in the export and import division in the form of written data which includes documents required for export activities. The results obtained in this research are that the analysis of procedures for abrasive cloth cargo export documents by PPJK at PT. Millennium Trans Bahari, in its implementation, is in accordance with existing procedures.